2017
DOI: 10.1109/tip.2017.2695898
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Quality of Fused Long Wave Infrared and Visible Light Images

Abstract: The capability to automatically evaluate the quality of long wave infrared (LWIR) and visible light images has the potential to play an important role in determining and controlling the quality of a resulting fused LWIR-visible light image. Extensive work has been conducted on studying the statistics of natural LWIR and visible images. Nonetheless, there has been little work done on analyzing the statistics of fused LWIR and visible images and associated distortions. In this paper, we analyze five multi-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Content may change prior to final publication. We conducted our human study following a similar procedure as described in [24], [25] and [26]. The set up was a single stimulus categorical rating [27].…”
Section: Srijmentioning
confidence: 99%
See 1 more Smart Citation
“…Content may change prior to final publication. We conducted our human study following a similar procedure as described in [24], [25] and [26]. The set up was a single stimulus categorical rating [27].…”
Section: Srijmentioning
confidence: 99%
“…It has been observed that natural images, under certain transformations, such as bandpass processing, or the removal of the lowest spatial frequency [32] strongly tend towards probability distributions that can be effectively captured using several (but ultimately equivalent) parametric density models. The Generalized Gaussian Distribution (GGD) and the Asymmetric Generalized Gaussian Distribution (AGGD) are examples of such statistical models that have been widely used in previous IQA studies [33], [34], [24], [26]. The GGD is defined as…”
Section: A Perceptual Featuresmentioning
confidence: 99%
“…We test the Gaussianity of the residual differences be tween the DMOS and 3D-IQA predictions after non-linear mapping, and use the F-statistic to compare the variance of the two distributions [76]. In particular the F-test is used to check if, under Gaussian distribution hypothesis, the residuals of two quality metrics being evaluated come from the same distribution and therefore are statistically indistinguishable [45,76,77]. The ratio between variances of the resid Farid et al Information Fusion xxx (2017) xxx-xxx uals of the two quality metrics is computed and compared with the F-ratio to determine their significance.…”
Section: Statistical Significance Testmentioning
confidence: 99%
“…NSS models of LWIR images have proven quite useful for a variety of visual tasks, such as IR image quality prediction, VL and IR image discrimination, analysis of IR-specific distortions (such as the halo effect), and thermal nonuniformities. More recently, the statistics of fused LWIR and VL images were analyzed, and a NSS-based algorithm for fused image quality assessment (IQA) was developed [22]. With this motivation, we seek to understand and model the NSS of X-ray images toward improving the solutions to many X-ray imaging problems.…”
Section: Introductionmentioning
confidence: 99%